Social position and minor psychiatric morbidity over time in the British Household Panel Survey 1991–1998. Issue 9 (13th August 2004) - Wiggins, R D; Schofield, P; Sacker, A; Head, J; Bartley, M
Abstract : Study objective: To examine social inequalities in minor psychiatric morbidity as measured by the GHQ-12 using lagged models of psychiatric morbidity and changing job status. Design: GHQ scores were modelled using two level hierarchical regression models with measurement occasions nested within individuals. The paper compares and contrasts three different ways of describing social position: income, social advantage and lifestyle (the Cambridge scale), and social class (the new National Statistics Socio-Economic Classification), and adjusts for attrition. Setting: Survey interviews for a nationally representative sample of adults of working age living in Britain. Participants: 8091 original adult respondents in 1991 who remain of working age during 1991–1998 from the British Household Panel Survey (BHPS). Main results: There was a relation of GHQ-12 to social position when social position was combined with employment status. This relation itself varied according to a person's psychological health in the previous year. Conclusions: The relation between social position and minor psychiatric morbidity depended on whether or not a person was employed, unemployed, or economically inactive. It was stronger in those with previously less good psychological health. Among employed men and women in good health, GHQ-12 varied little according to social class, status, or income. There was a "classic" social gradient in psychiatric morbidity, with worse health in less advantaged groups, among the economically inactive. Among the unemployed, a "reverse" gradient was found: the impact of unemployment on minor psychiatric morbidity was higher for those who were previously in a more advantaged social class position.